Performance Analysis of Half-Sweep Successive Over-Relaxation Iterative Method for Solving Four-Point Composite Closed Newton-Cotes Quadrature System - Muthuvalu, M.S. (IEEE Computer Society, 2017)
The theory and application of integral equations is an important subject within applied mathematics. Consequently, the main aim of this research paper is to investigate the performance of a variant of Successive Over-Relaxation iterative method i.e. Half-Sweep Successive Over-Relaxation (HSSOR) for solving four-point composite closed Newton-Cotes quadrature (4-CCNC) system that generated from linear Fredholm integral equations of the second kind. The numerical results from the simulations of the tested methods are presented. © 2016 IEEE.